The role of routine physiotherapy following open heart valve surgery in South Africans - De Charmoy, Suzanne (My University, 1998)
Post-operative physiotherapy for patients who have undergone uncomplicated coronary artery surgery has been shown to be of little value in preventing or restoring the abnormalities that occur in lung function, hypoxaemia, chest radiograph changes and length of post-operative hospital stay. This study aimed to establish whether similar results would be found for a group of patients undergoing cardiac valve surgery who had an uncomplicated post-operative course. The relevance of using valve surgery patients is that a very large number of state health care patienrs undergo valve surgery due to the remaining high incidence of rheumatic heart disease in South Africa. Thirty consecutive patients booked for elective valve surgery between June and September 1995 were included in the study once written informed consent had been obtained. The patients were then divided into two groups, a treatment group and a nontreatment !:,.roup. The treatment group received a regimen of breathing exercises, coughing and mobilisation tor the first four post-operative days while the non-treatment group were given a set of instructions to mobilise out of bed. The two groups were well matched tot' age, height, weight, body mass index and intraoperative details. Post-operatively arterial blood gas values, chest x-rays, temperature and length of stay were assessed to determine if there WaG any benefit to a regime of physiotherapy. The data was analysed using non-parametrical statistical tests and the